Morbidity and temporary cycles for the outpatient service at Universidad Estatal a Distancia in Costa Rica - Arce Espinoza, Lourdes (2008)
No data has apparently been published on morbidity and outpatient service of faculty and staff of a distance university.  This report presents such data from the Universidad Estatal a Distancia (Costa Rican State University for Distance Education). The participants in this study were the employees who were outpatients between January 15, 2004 and December 15, 2006.  Instead of using a sample, the entire population was studied with a total of 1,526 medical records. Procedure: During the first stage all of the medical records were read and the morbidity data was tabulated.  Subsequently, this information was statistically analyzed using Statgraphics Centurion XV. The main findings were that 50% of the patients used the outpatient service only once during the study period and that most of them were between 20 and 50 years of age.  The days with the most consultations were Mondays, Tuesdays, and Wednesdays.  The number of consultations was relatively stable throughout the year, with a slight increase in June. The three main causes for visiting the service were: upper respiratory tract diseases, muscular-skeletal disorders, and irritated digestive system problems. Main conclusions: Most of the consultations were from the departments with the more faculty and staff members; however, some departments had extremely high or low consultation rates per capita, maybe due to factors such as pathologies that require periodic control, geographical proximity, and psycho-social issues of patients who create a vicious circle due to the somatization of such problems.  The hypothesis that this population’s morbidity rate would differ from the national average because of its high educational level was rejected.  Nevertheless, the hypothesis that there are weekly and yearly cycles was maintained.